The Everyday Violence of Gendered Identities in Post-apartheid South Africa - Omarjee, Nadira; Ismail, Ghouwa; Malherbe, Nick; Mavundla, Bongani; Ngwenya, Nomagugu; Richardson, Pascal; Suffla, Shahnaaz (PINS-Psychology in Society, 2025)
In South Africa, everyday violence shapes and is shaped by a historically grounded enmeshment of gendered, racialised, and classed inequities, or what María Lugones referred to as the coloniality of gender. In contributing to scholarship on the coloniality of gender in South Africa, we conducted focus group discussions and individual interviews in two marginalised South African communities. Research participants highlighted how patriarchal social relations structure quotidian life. Specifically, they described how violence is used to reify masculinised identities (e.g., that of the breadwinner) and to ‘protect’ women from other violent men. Several participants interrogated the gendered systems of meaning that are normatively attached to such violence. By examining the discursive interplay of violence, gender, and impoverishment in the data, we conclude by considering how the coloniality of gender works to entrench hierarchical social ordering in contemporary South Africa. Accordingly, we advocate for structural and political change over individualising interventions.